Design of a fuzzy controller for a hybrid generation system (2020)
This paper presents the design of a control system for the automatic connection/disconnection and distribution of load, between an asynchronous alternator and a generator, in a hydroelectric central that works in isolated mode. The design of a control algorithm based on fuzzy logic is exposed, as this is a flexible method to be used in different installations with a variety of technology. The controller is supported on the Arduino Mega 2560 platform, in order to develop a low-cost system with its own technology, it is tested by computer simulation using the professional software Proteus v7.7, which guarantees that once validated the correct operation of the controller can be migrated to another system, say for example a PLC. The results obtained are shown and the simulations performed to the different blocks of the system are explained.